The Digital Business Ethics the Role of Government Policy on Tiktok Shop Indonesia License Revocation - Sigit Hariyanto; Amin Wahyudi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract: In This article discusses the role of the government in regulating digital business, focusing on the revocation of TikTok Shop licenses in Indonesia. Seeing the rapid development of digital business, digital business ethics is one of the main concerns. In the case of TikTok Shop license revocation, this article analyzes the role of the government in the policies that have been taken in order to create digital market economic stability. The author explains the background to this issue, including the rapid growth of TikTok Shop and its operating licenses. With the development of potential users who continue to increase, there is a violation of permissions by the TikTok application. In his analysis, the author highlights ethics in digital business and the role of government in creating economic stability in order to create broad value benefits to society. The method used in this study is qualitative with an in-depth literature approach. The results show that the importance of ethics in digital business and the important role of the government as a policy owner in regulating and supervising every technological development in order to protect the interests of the public and its relevance in the context of future regulatory development. Keywords: Digital Business Ethics, the Role of Government, Stability Economy